Open Space in Sub-District of Lebak Siliwangi, Bandung City, Indonesia - Sadikin, Pipin Noviati (Jurnal Sains Indonesia, 2023)
Some big parts of the world's population live in the city. While an increasing number population in the cities affects the demands for housing and settlements. But the housing is developed formally and informally. For informal settlements, one of the challenges is to provide open space for the community to do social activities. The objectives of the article are (1) to identify the typology of open spaces for the planning and design of a sustainable urban environment, city, and community, and (2) to recommend open space management in achieving the goal of SDGs 11.7 (provide universal access to safe, inclusive and accessible, green and public spaces, particularly for women and children, older persons and persons with disabilities). The method used is the literature review, interview, observation. The results showed that the Lebak Siliwangi Sub-District still needs to provide and manage the open space to accommodate community activities and social needs fulfilling. It is important to provide Common Open Spaces and Green Open Spaces to set up livelihood, lifestyles, and standards of community interaction for an urban community in informal settlements.